Results of Ponseti Brasil Program: Multicentric Study in 1621 Feet: Preliminary Results - Nogueira, Monica P.; Queiroz, Ana C.D.B.F.; Melanda, Alessandro G.; Tedesco, Ana P.; Brandão, Antonio L.G.; Beling, Claudio; Violante, Francisco H.; Brandão, Gilberto F.; Ferreira, Laura F.A.; Brambila, Leandro S.; Leite, Leopoldina M.; Zabeu, Jose L.; et al. (Wolters Kluwer, 2017)
Background: The Ponseti method has been shown to be the most effective treatment for congenital clubfoot. The current challenge is to establish sustainable national clubfoot treatment programs that utilize the Ponseti method and integrate it within a nation's governmental health system. The Brazilian Ponseti Program (Programa Ponseti Brasil) has increased awareness of the utility of the Ponseti method and has trained >500 Brazilian orthopaedic surgeons in it. Methods: A group of 18 of those surgeons had been able to reproduce the Ponseti clubfoot treatment, and compiled their initial results through structured spreadsheet. Results: The study compiled 1040 patients for a total of 1621 feet. The average follow-up time was 2.3 years with an average correction time of approximately 3 months. Patients required an average of 6.40 casts to achieve correction. Conclusions: This study demonstrates that good initial correction rates are reproducible after training; from 1040 patients only 1.4% required a posteromedial release. Level of Evidence: Level IV.
Keywords: clubfoot; conservative treatment; national program; outcomes; Ponseti method